Factors Related to the Implementation of Family Center Care in Critical Nursing Rooms at Karawang Hospital - Anton Priambodo; Henny Suzanna Mediani; Etika Emaliyawati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Nursing Services strive to provide a source of support for the patient’s family by implementing the Family Centered Care model in critical care rooms, focusing on providing family-centered nursing care services has not been fully applied in hospitals optimally. Objective: To Analyze the factors related to the implementation of family center care in critical nursing rooms at the Karawang district hospital. Methods: The research is a quantitative research with a correlational analytic descriptive research design with a cross-sectional design and the sample used is total sampling. The independent variables include Knowledge, Attitudes Bahavior and Facilities, while the dependent variable is Implementation of Family Center Care. Data analysis used univariate median tests, standard deviation or frequency, while bivariate tests used chi square and multivariate tests used logistic regression tests. Results: The results showed that the average implementation of Family Center Care was 64.00%, with the lowest implementation being 23% and the highest being 65%. From the bivariate results it was found that half of the respondents had good knowledge (57.4%), and more than half of the respondents had a supportive attitude (57.4%), complete facilities (68.5%), and good behavior (53.7%). The results of the logistic regression analysis showed that the implementation of Family Center Care by nurses in the critical care room was influenced by the most dominant factor, namely attitude, with a p-value (0.000) less than (0.05). Conclusion: In the study is that the implementation of Family Center Care by nurses in the Critical Care Room at Karawang Hospital is influenced by the attitude of the nurse, where from the supportive attitude of the nurse it can encourage the behavior of nurses towards the implementation of Family Center Care in the Critical Care Room at Karawang Hospital. With the implementation of Family Center Care properly, it will improve the quality nursing services.